Take me home [large type] - Garlock, Dorothy (Thorndike Press, 2014)
Life in Miller's Creek, Wisconsin, in 1945 is focused entirely on the war. Olivia Marsten does everything she can for the war effort and to support Billy, her childhood best friend who's leaving soon for Navy training. Then Billy confesses he's been in love with her for years and proposes. Olivia accepts, but she knows it isn't right. How do you break your best friend's heart, especially when you're secretly in love with a stranger?